Corrosion evaluation of CA-50 steel in pore waters extracted from cement pastes with steel slags using electrochemical techniques - Vieira,Renan Esposito (2021)
Abstract There is an interest in the cement industry in the use of steel slags in cement, but chemical and/or pyrometallurgical modifications are necessary to reduce the free CaO, MgO, and iron contents. However, the potential effects of its application in the reinforcement corrosion, whether in solid (concrete) or liquid medium (pore water), have not yet been addressed. In this context, the present study shows a corrosion analysis of the CA-50 steel in pore water medium extracted from cement pastes with 25% by weight of steel slag, in natural state or pyrometallurgical modified, by means of polarization curves, electrochemical impedance spectroscopy (EIS), and microstructural analysis. For comparison, tests were performed in pore waters presented in literature and representative from Ordinary Portland Cement (OPC) or activated Blast Furnace Slag (BFS) and, to simulate aggressive conditions, 1.0% NaCl was also added to the solutions. The steel remained passive in all media without 1.0% NaCl, but the EIS results indicated more protective characteristics in the medium simulating the modified steel slag. The main corrosion product identified by SEM images after the tests on aggressive media was lepidocrocite (γ-FeOOH), and the steel did not corrode in media with steel slags and 1.0% NaCl. This was attributed mainly to the higher alkalinity of these media in comparison to other usual pore waters, promoting longer protection of the steel.